2010
DOI: 10.2169/internalmedicine.49.3299
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Combination Therapy of Natural Human Interferon .BETA. and Ribavirin in Chronic Hepatitis C Patients with Genotype 2 and High Virus Load

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…TPA CC ITPA nonCC PEG-IFNα is known to often cause and exacerbate psychological problems (the range was reported to be from 30 to 80%) [19,20]. The incidence of nIFNβ-induced psychological problems has been reported to be from 0 to 10% [9][10][11]21]. In this study, 38.3 % (23 0f 60) of the patients who received nIFNβ plus RBV treatment suffered depression before treatment, but all of them completed treatment without increasing antidepressants or reduction of nIFNβ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPA CC ITPA nonCC PEG-IFNα is known to often cause and exacerbate psychological problems (the range was reported to be from 30 to 80%) [19,20]. The incidence of nIFNβ-induced psychological problems has been reported to be from 0 to 10% [9][10][11]21]. In this study, 38.3 % (23 0f 60) of the patients who received nIFNβ plus RBV treatment suffered depression before treatment, but all of them completed treatment without increasing antidepressants or reduction of nIFNβ.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with depression are not considered suitable for this combination treatment. In Japan, natural human interferon β (nIFNβ) and RBV combination treatment has been approved and recommended for depressed patients with chronic hepatitis C, and some studies have shown that nIFNβ plus RBV treatment has equivalent efficacy and mild adverse effects [9][10][11].…”
Section: Introductionmentioning
confidence: 99%